KETAHANAN PANGAN PERKOTAAN, KEMISKINAN, DAN COVID-19: KASUS KOTA BANDUNG - Mahra Arari Heryanto; Adi Nugraha (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The Covid-19 pandemic that hit Bandung City impacted increasing poverty rates and unemployment rates due to negative economic growth. The decline in purchasing power impacts declining people's access to food. For low-income communities, decreasing access to food means reducing the quantity and quality of food consumed. This paper discusses the food security of urban communities affected by the crisis due to the Covid-19 pandemic. By using the system thinking approach, exploration is held by analyzing events, behavior patterns, and system structures. The results of this study indicate that the macroeconomic system plays a significant role in the food security of urban communities. There are several mutually reinforcing feedback loops between macroeconomics and food security: purchasing power, food access and food consumption. As the vulnerable group most affected by the pandemic, the fulfillment of nutrition for low-income groups is still below the recommended nutritional adequacy standard (2,150 kilo calories per capita per day). Another finding of this study is a comprehensive CLD on urban food security systems. The CLD can describe the interdisciplinary roles between actors to fulfill basic human needs: food. In addition, besides macroeconomics and agriculture, food security is also closely related to health, environment, and trade.